Socialization of Tips to Avoid Predatory Journals in Improving the Quality of Student and Lecturer Workload Reports: Pengabdian - Dian Wahyuningsih; M. Syahputra; Nurjanna Ladjin; Siti Kholidah Marbun; Rusdianto (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
During the socialization of five hundred students spread across several campuses, namely: for ten days at Langlangbuana University, Syedza Saintika University, Muhammadiyah University of Luwuk, Mandaling Natal State Islamic College, and Tamansiswa University Palembang. These eight characteristics, which are among the materials used in the author's outreach program, are hoped to serve as a primary reference for finding accredited and high-quality academic journals and helping to avoid predatory journals. The author sincerely hopes that participants in this outreach program will improve their reading literacy, enhance their thinking paradigms, and enhance the quality of their writing.